Comparison of the carbon sequestration potential of young Tectona grandis L. f. (Teak) and Dendrocalamus strictus (Roxb.) Nees (Bamboo) plantations in the landscape of central India - Keren, Gone Arpana; Chaudhry, Pradeep; Sharma, Atul; Singh, Sudeep (Ecological Questions, 2019)
The Kyoto Protocol addresses the issues related to global warming and it is the responsibility of the signatory countries to protect the sinks and reservoirs of greenhouse gases, to increase forest plantations and to promote sustainable forest management. India is also one of the signatories of the Kyoto Protocol, which is why various forest plantations have been established in the country. The present study compares the carbon sequestration potential of three-year-old Tectona grandis (teak) and Dendrocalamus strictus (bamboo) plantations in the state of Madhya Pradesh of India. It is concluded that D strictus sequesters more carbon than T. grandis and both species are suited for plantations in tropical areas of India.